2011
DOI: 10.1038/nature10331
|View full text |Cite
|
Sign up to set email alerts
|

Protection of repetitive DNA borders from self-induced meiotic instability

Abstract: DNA double strand breaks (DSBs) in repetitive sequences are a potent source of genomic instability, due to the possibility of non-allelic homologous recombination (NAHR). Repetitive sequences are especially at risk during meiosis, when numerous programmed DSBs are introduced into the genome to initiate meiotic recombination 1. Within the budding yeast repetitive ribosomal (r)DNA array, meiotic DSB formation is prevented in part through Sir2-dependent heterochromatin 2,3. Here, we demonstrate that the edges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(180 citation statements)
references
References 30 publications
13
164
3
Order By: Relevance
“…Pch2 is a conserved AAA+ ATPase that maintains the nonuniform pattern of Hop1 occupancy along meiotic chromosomes (Bö rner et al, 2008;Joshi et al, 2009). The different Hop1 occupancies seen in wild type were preserved early in meiosis in pch2D mutants ( Figure 4A, Figure 4-figure supplement 1A), consistent with previous findings that, in pch2 cells, Spo11-DSB patterns are not altered in most regions of the genome (Vader et al, 2011). By contrast, at later times (4-5 hr after initiation of meiosis), pch2D mutants displayed reduced Hop1 occupancy at HIS4, more closely approaching the lower occupancy levels seen throughout meiosis at URA3 ( Figure 4A; Figure 4-figure supplement 1A).…”
Section: Altered Hop1 Occupancy In Pch2 Mutants Is Associated With Alsupporting
confidence: 80%
“…Pch2 is a conserved AAA+ ATPase that maintains the nonuniform pattern of Hop1 occupancy along meiotic chromosomes (Bö rner et al, 2008;Joshi et al, 2009). The different Hop1 occupancies seen in wild type were preserved early in meiosis in pch2D mutants ( Figure 4A, Figure 4-figure supplement 1A), consistent with previous findings that, in pch2 cells, Spo11-DSB patterns are not altered in most regions of the genome (Vader et al, 2011). By contrast, at later times (4-5 hr after initiation of meiosis), pch2D mutants displayed reduced Hop1 occupancy at HIS4, more closely approaching the lower occupancy levels seen throughout meiosis at URA3 ( Figure 4A; Figure 4-figure supplement 1A).…”
Section: Altered Hop1 Occupancy In Pch2 Mutants Is Associated With Alsupporting
confidence: 80%
“…The abundant gene conversions in Arabidopsis suggest that plants are more like mammals (7) than yeast, the latter having relatively common crossing-over compared with gene conversion (6). This difference between taxa we suggest may reflect differences in repeat content, as repetitive sequences are a source of genomic instability during meiosis (27), owing to nonallelic homologous recombination (28). Compared with COs, non-CO [e.g., via SDSA (2)], which yields the most gene conversions, poses the least genomic threat among mechanisms that repair DSBs (29).…”
Section: Discussionmentioning
confidence: 91%
“…Repetitive DNA is known to be a major source of genome instability in various organisms due to hyperrecombination events as a result of replication stress (Bzymek and Lovett 2001;Vader et al 2011). In Neurospora, the repetitive rDNA locus is a site of frequent chromosome breakage (Butler 1992), and we previously showed that the replication process is required for qiRNA production ).…”
Section: Genes and Development 533mentioning
confidence: 99%